(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Acetaldehyde is naturally found in many foods such as dairy products and coffee. It is also used as a flavoring agent in milk products, sweets and juices including soft drinks. Acetaldehyde is classified as carcinogen to humans (group B2) additionally it affects yogurt flavor. Yogurt is a widely consumed milk product in the local market and it is one of the important exposure sources to acetaldehyde. Yogurt is obtained by fermenting milk using specific bacterial strains of lactic acid bacteria that metabolize lactose and turn it into many products such as acetaldehyde. This study aims to determine the levels of acetaldehyde in some yogurt samples using the titration method. Acetaldehyde was not detected in samples of cow milk, both full fat or low fat. The amount of acetaldehyde in cow milk ranged between 1.34 and 41.26 mg/kg, in (Ayran) samples it ranged between 5.32 and 11.2 mg/kg, while (Labneh) samples contained 2.57 to 5.5 mg/kg, and finally sheep milk samples contained between 20.81and 40.53 mg/kg. The storage of Yogurt for a week resulted in a gradual decrease of acetaldehyde.